Grain hordein content and malt quality as affected by foliar nitrogen fertilisation at heading - Prystupa, Pablo (2021)
Nitrogen fertilisation at heading is a practice for increasing grain protein content in malting barley. The objective of this study was to assess the effects of fertilisation on grain protein, the content and composition of hordeins, and relationship to malt quality. In 25 field experiments in the Argentine Pampas, the effect of foliar nitrogen fertilisation at heading on the grain protein content was evaluated. In five experiments, the content and composition of hordeins and some malting quality indices was assessed. Nitrogen fertilisation at heading increased grain protein content, hordein content and the proportion of hordein C, and decreased the proportion of hordein B. In addition, malts obtained from the grains of the crops fertilised with nitrogen at heading had lower extract and higher hardness than those obtained without fertilisation. Malt extract was negatively associated with total hordein (or protein) content and positively with grain size. The inclusion of the fractions into which hordeins are classified did not improve the explanatory models for malt extract. Therefore, the composition of hordein does not seem to be a determining factor for malt extract when comparing samples with and without nitrogen fertilisation at heading. © 2021 The Institute of Brewing & Distilling.